Stimulating the student’s reflection - Nguyen, Hung Hoa (Đại học Quốc gia Hà Nội, 2020)
The importance of reflection is frequently noted in the literature. Reflective competence is regarded by many educators as an essential characteristic for professional education. Activities to promote reflection were limited because of the misunderstanding about reflection’s definition and the complicated model of reflection. We, therefore, designed a literature review to clarify the definition and model of reflection. The aim of this paper was to construct situation to stimulate Vietnamese students’ reflection.